Corallivory in the Anthropocene: Interactive Effects of Anthropogenic Stressors and Corallivory on Coral Reefs - Rice, Mallory M.; Ezzat, Leïla; Burkepile, Deron E. (Frontiers in Marine Science, 2019)
Corallivory is the predation of coral mucus, tissue, and skeleton by fishes and invertebrates, and a source of chronic stress for many reef-building coral species. Corallivores often prey on corals repeatedly, and this predation induces wounds that require extensive cellular resources to heal. The effects of corallivory on coral growth, reproduction, and community dynamics are well-documented, and often result in reduced growth rates and fitness. Given the degree of anthropogenic pressures that threaten coral reefs, it is now imperative to focus on understanding how corallivory interacts with anthropogenic forces to alter coral health and community dynamics. For example, coral bleaching events that stem from global climate change often reduce preferred corals species for many corallivorous fishes. These reductions in preferred prey may result in declines in populations of more specialized corallivores while more generalist corallivores may increase. Corallivory may also make corals more susceptible to thermal stress and exacerbate bleaching. At local scales, overfishing depletes corallivorous fish stocks, reducing fish corallivory and bioerosion, whilst removing invertivorous fishes and allowing population increases in invertebrate corallivores (e.g., urchins, Drupella spp.). Interactive effects of local stressors, such as overfishing and nutrient pollution, can alter the effect of corallivory by increasing coral-algal competition and destabilizing the coral microbiome, subsequently leading to coral disease and mortality. Here, we synthesize recent literature of how global climate change and local stressors affect corallivore populations and shape the patterns and effect of corallivory. Our review indicates that the combined effects of corallivory and anthropogenic pressures may be underappreciated and that these interactions often drive changes in coral reefs on scales from ecosystems to microbes. Understanding the ecology of coral reefs in the Anthropocene will require an increased focus on how anthropogenic forcing alters biotic interactions, such as corallivory, and the resulting cascading effects on corals and reef ecosystems.